2007
DOI: 10.1105/tpc.106.044404
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Participation of Red Chlorophyll Catabolite Reductase in Chlorophyll Breakdown

Abstract: A central reaction of chlorophyll breakdown, porphyrin ring opening of pheophorbide a to the primary fluorescent chlorophyll catabolite (pFCC), requires pheophorbide a oxygenase (PAO) and red chlorophyll catabolite reductase (RCCR), with red chlorophyll catabolite (RCC) as a presumably PAO-bound intermediate. In subsequent steps, pFCC is converted to different fluorescent chlorophyll catabolites (FCCs) and nonfluorescent chlorophyll catabolites (NCCs). Here, we show that RCCR-deficient Arabidopsis thaliana acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
233
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 222 publications
(242 citation statements)
references
References 76 publications
6
233
2
1
Order By: Relevance
“…PAO activity was monitored in vitro essentially as described (Pružinská et al, 2007) but using 0.06 μg μl -1 of His 6 -AtRCCR (Pružinská et al, 2007), and 100 U of catalase (Sigma) to replace red chl catabolite-forming factor (Pružinská et al, 2005). pFCC formation was followed by reversed-phase HPLC and fluorescence detection (320/450 nm) using 36% (v/v) 50 mM potassium phosphate buffer, pH 7, in methanol as solvent (Pružinská et al, 2005).…”
Section: Analysis Of Chl and Chl Catabolitesmentioning
confidence: 99%
“…PAO activity was monitored in vitro essentially as described (Pružinská et al, 2007) but using 0.06 μg μl -1 of His 6 -AtRCCR (Pružinská et al, 2007), and 100 U of catalase (Sigma) to replace red chl catabolite-forming factor (Pružinská et al, 2005). pFCC formation was followed by reversed-phase HPLC and fluorescence detection (320/450 nm) using 36% (v/v) 50 mM potassium phosphate buffer, pH 7, in methanol as solvent (Pružinská et al, 2005).…”
Section: Analysis Of Chl and Chl Catabolitesmentioning
confidence: 99%
“…Indeed, in an identical assay, but using epi-pFCC instead of pheophorbide a as substrate, the polar FCC fraction increased in a timedependent manner ( Figure 2B). To confirm identity of this compound as hydroxy-epi-pFCC, we compared its retention time in HPLC with the retention times of the FCCs accumulating in gerontoplasts of Col-0 plants and of acd-22+At-RCCR-X plants (Pruzinská et al, 2007) that were complemented with the epipFCC-producing "X" version of Arabidopsis RCCR (see Introduction). Coinjection experiments indeed confirmed that the product of in vitro hydroxylation of epi-pFCC is identical to the polar FCC fraction from acd2-2+At-RCCR-X chloroplasts ( Figure 2C).…”
Section: Hydroxy-pfcc Is Present In Gerontoplasts Of Arabidopsismentioning
confidence: 99%
“…PAO, in concert with red chlorophyll catabolite reductase (RCCR), catalyzes the ring-opening reaction of pheophorbide a, the phytol-and Mg-free intermediate of the early part of chlorophyll breakdown, to a primary fluorescent chlorophyll catabolite (pFCC), the primary (fluorescent) phyllobilin that is the precursor of all subsequently formed phyllobilins. The direct product of the PAO reaction, red chlorophyll catabolite, does not accumulate but is immediately reduced at the C15/C16-double bond by RCCR in an intriguing stereospecific manner (Wüthrich et al, 2000;Pruzinská et al, 2007) (for atom and pyrrole numbering of phyllobilins, see the structure of pFCC in Figure 1B). Thus, depending on the source of the enzyme, two C16-stereoisomers, pFCC or epi-pFCC, may occur (Mühlecker et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whereas many basic aspects of the path(s) of their formation remain obscure, key structural elements present in 1 and 2 are compatible with a role of an RCC8b, 15 and of FCCs16 as their precursors. Genomic analysis of ferns has, indeed, provided evidence for proteins related to the enzymes PaO17 and RCCR18 in these seedless higher plants,9 crucial for formation of hypothetical PBs, such as RCC and “primary” FCC. Hence, the biochemical pathway to FCC‐type intermediates may be available in the chloroplasts of ferns.…”
mentioning
confidence: 99%